تأثير نشاط الطلاب فى دراسة طريقة يسرنا على كفاية قراءة الكتب في معهد عبد الحميد صالح الإسلامي كيانجان جومبانج - Raihanah, Rifkoh; Azhari, Muhammad Yahya; Amrullah, Amrullah (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2024)
The activeness of students in the learning process, it is necessary to involve students in the form of attitudes, thoughts, and actions of students to optimize the potential of students, especially the ability to read books to achieve satisfactory learning outcomes by their characteristics. The purpose of this study was to determine the influence of student activity in the study of the Yassarnaa method on the ability to read books at the Abdul Hamid Sholeh Kayangan Jombang Islamic Boarding School. This study uses quantitative methods with simple linear regression analysis. The data collection technique uses questionnaires, interviews, and documentation. The results showed that calculations using a simple linear regression formula obtained a calculated t value with a tablet of 2,140 t tables > 2,035, then Ha was accepted and H0 was rejected, it can be concluded that the activeness of students in the study of the Yassarnaa method on the ability to read the book had a significant influence. The percentage of respondents' answers about the activeness of students in the study of the Yassarnaa method on the ability to read books obtained a score of 93.75% of the 35 respondents' answers.